Optimalisasi Media Digital dalam Pengelolaan Public Relations di UIN Raden Mas Said Surakarta - Atiya Aena Rahma; Wisnu Widjanarko; Wiwik Novianti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The advancement of digital communication technology has significantly transformed public relations practices, particularly within higher educations institutions. This study aims to explore how digital media optimized in managing public relations at UIN Raden Mas Said Surakarta. Using a gualitative descriotive approach within the constructivist paradigm, data were collected through in depth interviews with the head and staff of the Public Relations Division, as well as documentation of digital communication activities. The findings show that Uin Raden Mas Said Surakarta has implemented an integrated Digital Public Relations strategy tha combines informative, persuasive and educational content across social media platforms. This digital approach effectively strenghens institusional image, build public engagement and enchaces brand awareness. However, the study also indentifies challenges related to limited human resources and the sustainability of content management. Overall, the optimization of digital media in public relations contributes to improving institutional credibility and supports the realization of transparent, interactive and sustainable public communication.